2012
DOI: 10.1177/0894845312470025
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of Career Aspirations in Thai Children in an International School in Bangkok

Abstract: This investigation employed exploratory methods to examine career aspirations in 141 students in Grades 4, 6, 8, 10, and 12 from an international school in Bangkok. Students specified the jobs that they were most likely to pursue as adults, rated the importance of potential influences in making career decisions, and drew a picture of themselves in their future occupations. Students aspired to a range of careers and viewed their own abilities and interests as being of primary importance in choosing a career tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…This point provokes the question: What are the global ideologies to which young people in far-flung regions of the world increasingly identify, and what are the local ideologies that young people maintain? Global values are presently conceptualized as those values that empirical and theoretical scholarship have associated with globalization, including the following: choice and agency, commerce and capitalism, democracy, egalitarianism, individualism, international travel and dwelling, material consumption, mobility and migration, pursuit of happiness and high-arousal positive affective states, self-development, and selfexpression (Arnett, 2002;Greenfield, 2009;Jensen et al, 2011;Manago et al, 2015;McDevitt et al, 2013;McKenzie, 2019a;McKenzie, Rooney, et al, 2019;Rao et al, 2013;Uchida & Ogihara, 2012). Though such values generally typify WEIRD (Western, Educated, Industrialized, Rich, Democratic) societies (Henrich et al, 2010), modern globalization has widened their spread.…”
Section: Youth Development In Contexts Of Globalizationmentioning
confidence: 99%
“…This point provokes the question: What are the global ideologies to which young people in far-flung regions of the world increasingly identify, and what are the local ideologies that young people maintain? Global values are presently conceptualized as those values that empirical and theoretical scholarship have associated with globalization, including the following: choice and agency, commerce and capitalism, democracy, egalitarianism, individualism, international travel and dwelling, material consumption, mobility and migration, pursuit of happiness and high-arousal positive affective states, self-development, and selfexpression (Arnett, 2002;Greenfield, 2009;Jensen et al, 2011;Manago et al, 2015;McDevitt et al, 2013;McKenzie, 2019a;McKenzie, Rooney, et al, 2019;Rao et al, 2013;Uchida & Ogihara, 2012). Though such values generally typify WEIRD (Western, Educated, Industrialized, Rich, Democratic) societies (Henrich et al, 2010), modern globalization has widened their spread.…”
Section: Youth Development In Contexts Of Globalizationmentioning
confidence: 99%
“…In future research, the relationship between career aspirations and female Thai student's backgrounds (e.g., socioeconomic levels, academic abilities) could be examined and compared with the career aspirations of women from disadvantaged and advantaged families. To be able to give efficacious guidance that can support students of various backgrounds to formulate ambitious career goals (McDevitt, Hess, Leesatayakun, Sheehan, & Kaufeld, 2013).…”
Section: Future Study and Implicationmentioning
confidence: 99%
“…This is consistent with the work of Hoskins and Barker (2014) finding that young people's identities and aspirations drew from their varied sources of capital. It also adds to the work done by McDevitt et al (2013) who found parents do shape the career aspirations of their children. This would also resonate with Leighton (2013) who puts forth that children of judges and politicians might be doing more than following a family tradition, just as miners followed miners and farmers followed farmers through generations (Leighton 2013: 426).…”
Section: Sub-theme Which Addresses the Research Question: Familymentioning
confidence: 91%
“…In their findings however, they recommend that an investigation be conducted examining the influence international schooling has on the aspirations of local students. In an investigative study into the careers aspirations of Thai children who attended an international school in Bangkok, McDevitt et al (2013) found that students aspired to a range of careers and viewed their own abilities and interests as being of importance in choosing a career track (McDevitt et al 2013: 531). More recently, Bailey (2015) conducted a small-scale study of host country nationals attending an international school in Malaysia.…”
Section: An Elite Educationmentioning
confidence: 99%